The Effects of Cumulative Dose and Polymorphisms in CYP2B6 on the Mitotane Plasma Trough Concentrations in Chinese Patients With Advanced Adrenocortical Carcinoma - Liu, Xin; Shang, Junmei; Fu, Qiang; Lu, Lin; Deng, Jianhua; Tang, Yan; Li, Jiantao; Mei, Dan; Zhang, Bo; Zhang, Shuyang (Frontiers in Oncology, 2022)
Mitotane is the only drug approved to treat adrenocortical carcinoma (ACC), and a relationship of pharmacokinetic/pharmacodynamic has been characterized. However, limited evidence concerning affecting factors in large interindividual variability of the pharmacokinetics of mitotane is available. To address this question, a retrospective analysis was performed on ACC Chinese patients treated with mitotane for more than 3 months. Mitotane plasma trough concentrations were detected at the steady state, and CYP2B6, CYP3A4, and pregnane X receptor (PXR) polymorphisms were genotyped. After examining homogeneous pharmacologic data, we restricted the analyses to 36 patients that received mitotane for a median (interquartile range, IQR) of 9 months (5.00–22.50) with a median dose of 2 g/day (2.00–2.50). As a result, drug exposure was significantly influenced by the cumulative dose of mitotane, and CYP2B6 516GG and CYP2B6 26570CC were at high risk to be below the therapeutic range of mitotane. No association was found between mitotane concentrations with CYP3A4 or PXR polymorphism. Our data firstly indicated that the cumulative dose of mitotane and polymorphisms of CYP2B6 516 and CYP2B6 26570 might significantly affect mitotane plasma trough concentrations in Chinese ACC patients.